THE ANALYSIS OF PROCESS IN SELECTED SPEECHES OF PRESIDENT SUSILO BAMBANG YUDHOYONO - Margareth Fransisca Sinaga; Elia Masa Gintings (State University of Medan, 2013)
Abstract One aim of this article is to show many kinds of speeches of process in speech. The example of speech is the speech of President Susilo Bambang Yudhoyono. The purpose of this journal is to find out types of processes, they are; material process, mental process, relational process, behavioral process, verbal process, and existential process. It was found that the types of processes in the five speeches of President Bambang Yudhoyono are 1387 verbs and classified the verb into 868 verbs as Material process (62.58%), 46 verbs as Mental process (3.31%), 130 verbs as Relational process (9.37%), 208 verbs as Behavioral process (15%), 25 verbs as Verbal process (1.80%), and 110 verbs as Existential process (7.94%). From the data, it could be known that the dominant process in the selected speech of President Susilo Bambang Yudhoyono was Material process. Keywords: process; speech